2009
DOI: 10.1026/0012-1924.55.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Geschützte Werte Skala (GWS)

Abstract: Zusammenfassung. Geschützte Werte (GW) sind Werte, die von Individuen oder einer Gemeinschaft als absolut, unantastbar und nicht substituierbar angesehen werden. Da es bislang noch kein Messinstrument zur Erfassung von GW gibt, besteht das Ziel der vorliegenden Arbeit in der Entwicklung und ersten Validierung einer Geschützten Werte Skala (GWS). Die in Studie 1 durchgeführten Analysen zur Überprüfung der Skalen und der Modellgüte fallen zufrieden stellend aus. Im Sinne der diskriminativen Validität kann gezeig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…People think of such values as absolute, nonsubstitutable, and above all price (Kant, 1785/1977). Empirical psychologists use the concept of sacred values (SVs; or, protected values) to refer to these core values to which people feel strongly committed to and which they wish to defend against cost–benefit calculations (Atran, Axelrod, & Davis, 2007; Baron & Spranca, 1997; Tanner, Medin, & Iliev, 2008; Tanner, Ryf, & Hanselmann, 2009; Tetlock, Kristel, Elson, Green, & Lerner, 2000). In particular, empirical research has shown that SV violations tend to be associated with strong emotional reactions, such as moral outrage or disgust (Tetlock et al, 2000).…”
mentioning
confidence: 99%
“…People think of such values as absolute, nonsubstitutable, and above all price (Kant, 1785/1977). Empirical psychologists use the concept of sacred values (SVs; or, protected values) to refer to these core values to which people feel strongly committed to and which they wish to defend against cost–benefit calculations (Atran, Axelrod, & Davis, 2007; Baron & Spranca, 1997; Tanner, Medin, & Iliev, 2008; Tanner, Ryf, & Hanselmann, 2009; Tetlock, Kristel, Elson, Green, & Lerner, 2000). In particular, empirical research has shown that SV violations tend to be associated with strong emotional reactions, such as moral outrage or disgust (Tetlock et al, 2000).…”
mentioning
confidence: 99%
“…The items were adjusted to the specific content of each vignette (see Appendix). To assess affective responses, and drawing on previous scales (Tanner et al, 2009;Tetlock et al, 2000), participants rated the extent to which they would perceive the decision made in the corresponding vignette as outrageous, shameful, acceptable, or praiseworthy (4 items, the latter two items reverse-coded). For example, regarding a situation in which the son of a client has applied belatedly for a job position in the company, participants were asked "To which extent would you judge it as outrageous if the client's son had been chosen for the position?…”
Section: Methodsmentioning
confidence: 99%
“…Sacred values were assessed using the GWS‐D scale . The items turned out to load on two different factors, with the two negatively formulated items (Items 4 and 5) loading on a different factor.…”
Section: Methodsmentioning
confidence: 99%
“…Sacred values were assessed using the GWS-D scale. (29) The items turned out to load on two different factors, with the two negatively formulated items (Items 4 and 5) loading on a different factor. Consequently, a scale without these two items would have a higher Chronbach's Alpha (0.744 instead of 0.699).…”
Section: Data-gathering Instrumentsmentioning
confidence: 99%